2002
DOI: 10.1016/s0014-5793(02)03488-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered shoot/root Na+ distribution and bifurcating salt sensitivity in Arabidopsis by genetic disruption of the Na+ transporter AtHKT1

Abstract: Sodium (Na + ) is toxic to most plants, but the molecular mechanisms of plant Na + uptake and distribution remain largely unknown. Here we analyze Arabidopsis lines disrupted in the Na + transporter AtHKT1. AtHKT1 is expressed in the root stele and leaf vasculature. athkt1 null plants exhibit lower root Na + levels and are more salt resistant than wild-type in short-term root growth assays. In shoot tissues, however, athkt1 disruption produces higher Na + levels, and athkt1 and athkt1/ sos3 shoots are Na + -hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
344
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(373 citation statements)
references
References 32 publications
29
344
0
Order By: Relevance
“…In theory, the amount of K + and Na + in leaves is determined by several distinct processes: Na + /K + uptake from the soil, longdistance transport to the shoot via the xylem, and redistribution through the phloem. The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, the amount of K + and Na + in leaves is determined by several distinct processes: Na + /K + uptake from the soil, longdistance transport to the shoot via the xylem, and redistribution through the phloem. The function of xylem-localized HKT1 in limiting Na + translocation to the shoot has been established (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006;Davenport et al, 2007). In hkt1 mutants, xylem Na + concentration is higher than in the wild type (Sunarpi et al, 2005).…”
Section: Phloem and Na + /K + Homeostasismentioning
confidence: 99%
“…Based on the phenotype of Arabidopsis thaliana sodium overaccumulation in shoot2 (sas2 allele of HKT1) mutants, Na + transporter HKT1 was proposed to function in the phloem (Berthomieu et al, 2003). However, the current consensus is that HKT1 mainly functions to remove Na + from the xylem, thus limiting Na + accumulation in leaves (Mä ser et al, 2002;Sunarpi et al, 2005;Rus et al, 2006). The extent and mechanism of Na + translocation in the phloem remains unknown and has been identified as a current research topic that is important for understanding Na + tolerance (Munns and Tester, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…sas2-1 mutation impaired AtHKT1 and thus its Na + transport activity in Xenopus oocytes (83). T-DNA mutation in the AtHKT1 gene has resulted in higher shoot Na + content and lower root Na + content than that in the wild type (84). Moreover AtHKT1 does not show significant K + transport activity in Xenopus oocytes.…”
Section: Sodium Transport From Shoots To Rootsmentioning
confidence: 99%
“…In our research into salinity stress of plants, we have identified a sodium cation transporter family in plants called HKT transporters and using the plant Arabidopsis thaliana showed that the AtHKT1 transporter plays a key role in protecting plant leaves from sodium over-accumulation and salt stress [2]. We found that AtHKT1 protects leaves from sodium accumulation by removing sodium from the xylem sap [3,4].…”
Section: What Is the Main Focus Of Your Studies?mentioning
confidence: 99%
“…We and colleagues are pursuing research to identify the transporters for the vacuolar heavy metal chelating and detoxifying peptides called phytochelatins. These transporters have been sought for some 15 years and are key mechanisms that plants use to withstand toxic heavy metals.In our research into salinity stress of plants, we have identified a sodium cation transporter family in plants called HKT transporters and using the plant Arabidopsis thaliana showed that the AtHKT1 transporter plays a key role in protecting plant leaves from sodium over-accumulation and salt stress [2]. We found that AtHKT1 protects leaves from sodium accumulation by removing sodium from the xylem sap [3,4].…”
mentioning
confidence: 99%